Psychological assessment of professional performance in the structure of human resource management of organization - Avanesyan, Hrant; Davtyan, Araksya (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article discusses the problem of psychological assessment of personnel in the ways of communication between the characteristic features of employees, the specifics of their motivational-value sphere and performance, taking into account the understanding of the regulatory in the context of human resource management of the organization. Ensuring the effectiveness of the use of advanced training methods in the selection process and further training in order to increase the efficiency of the use of advanced training methods. The author’s research and analysis of similar works have shown that, depending on the professional activity, psychological qualities of the personality, the motivational component, the level of self-regulation of voluntary activity, the degree of preparedness, professional competence, the dynamics of individual stages of working capacity can be maintained in accordance with the intensity of work or stages of work cycles.